Aplikasi Capital Budgeting dalam Penentuan Keputusan Investasi Kamar dan Ballroom Di Hotel Panorama Lembang - Wardhana, Wishnu (Jurnal Kepariwisataan: Destinasi, Hospitalitas dan Perjalanan, 2018)
This research's title is "Applications of Capital Budgeting Method in Feasibility Study of Rooms and Ballroom Investment at Hotel Panorama Lembang", the purpose of this research are to know the feasibility of hotel investment based on financial projection aspect which using Capital Budgeting Method at Hotel Panorama Lembang. The feasibility of investment evaluate by the tools of capital budgeting model, which is have aspect of Discounted Payback Period, Net Present Value, Internal Rate Of Return, and Profitability Index in Hotel Panorama Lembang. The results of this research from the financial projection evaluated with the tools of capital budgeting evaluation which have the results can be seen that investment is feasible, as calculated by the method of discounted payback period is 8 years and 2 months based on hotel evaluation and 6 years and 11 months based on writer's evaluation, net present value in positive result (NPV > 0) in the amount of Rp. 1.743.693.325 , Internal Rate of Return is higher than the discounted factor of 12% in the amount of 23.9303%, profitability index is in positive result higher than 1. Based upon this calculation summarised that the feasibilty of investment based on financial projection are accepted. Based on the evaluation from the capital budgeting method, the criteria of investment at Hotel Panorama Lembang are accepted. The management used the methods which doesn't improve a good result in feasibility. Methods that used by the author more improve a good result in investing decisions, because using a selection of forecasting methods for future revenues. The author used a time series forecasting methods to improve more revenues for hotel. This forecasting method can provide the closest forecast result and the highest rate of accuracy. The author recommends to the management of Panorama Hotel Lembang to continue and accepted the investment of new rooms and ballroom. Considering the result of a feasebility study with a capital budgeting methods are accepted. The author also recommends to the management of Panorama Hotel Lembang to use a proper forecasting methods, such as time series methods.